Neferine Protects Endothelial Glycocalyx via Mitochondrial ROS in Lipopolysaccharide-Induced Acute Respiratory Distress Syndrome - Liu, Xiang-Yong; Xu, Hai-Xiao; Li, Jian-Kui; Zhang, Dong; Ma, Xiao-Hong; Huang, Li-Na; Lü, Jun-Hong; Wang, Xiao-Zhi (Frontiers in Physiology, 2018)
Damage to the endothelial glycocalyx is a critical factor in increased pulmonary vascular permeability, which is the basic pathological feature of acute respiratory distress syndrome (ARDS). Neferine (Nef), a bisbenzylisoquinoline alkaloid isolated from green seed embryos of Nelumbo nucifera Gaertn, has extensive pharmacological activity. In this study, we showed that Nef reduced lung-capillary permeability, down-regulated the production of cytokines (IL-1β, IL-6, TNF-α and IL-10) and inhibited the activation of the NF-κB signaling pathway in mice with lipopolysaccharide (LPS)-induced ARDS. Further analysis indicated that Nef provided protection against endothelial glycocalyx degradation in LPS-induced ARDS mice (in vivo) and in LPS-stimulated human umbilical vein endothelial cells (in vitro). The glycocalyx-protective effect of Nef may be initiated by suppressing the production of mitochondrial ROS (mtROS) and decreasing oxidative damage. Nef was also found to promote glycocalyx restoration by accelerating the removal of mtROS in endothelial cells in LPS-induced ARDS. These results suggested the potential of Nef as a therapeutic agent for ARDS associated with Gram-negative bacterial infections and elucidated the mechanisms underlying the protection and restoration of the endothelial glycocalyx.